What determines coal consumption for residential heating in Kazakhstan and the Kyrgyz Republic?. Issue 4 (2nd October 2021) - Azhgaliyeva, Dina; Mishra, Ranjeeta; Karymshakov, Kamalbek; Kerimray, Aiymgul; Kapsalyamova, Zhanna
ABSTRACT: Solid fuels, such as coal and firewood, account for a large share of residential heating fuel consumption in Kazakhstan and the Kyrgyz Republic. Solid fuels used for residential space heating are a major source of indoor air pollution, which impose health risks. Using microdata from the national household surveys from Kazakhstan in 2018 and the Kyrgyz Republic in 2016, this study examines the factors affecting the choice of residential heating. We employ two models: logit and double-hurdle. The results show that access to cleaner and more modern energy infrastructure such as natural gas pipelines and district heating reduces solid fuel consumption, especially in rural areas. Regions with higher coal prices prefer cleaner heating, while regions with higher electricity prices are more likely to participate in the coal markets. Female-headed households are less likely to use coal.